Terraform and AWS CDK: A Comparative Analysis of Infrastructure Management Tools - Frois, João; Padrão, Lucas; Oliveira, Johnatan; Xavier, Laerte; Tavares, Cleiton (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Infrastructure as Code is a fundamental concept in DevOps that automates infrastructure management processes using code. Several tools, such as Terraform and CDK, support this environment. Selecting the appropriate tool is crucial to a project’s success, yet there is ambiguity about the circumstances in which developers should choose between these tools. Therefore, this study aims to compare Terraform and CDK across four aspects: abstraction, scalability, maintainability, and performance. Our findings indicate that each tool performs particularly well in specific scenarios. For instance, Terraform is better suited for experienced teams focused on rapid implementations, while CDK is more appropriate for less experienced teams prioritizing resource efficiency during implementation.